If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying p + -5 = 9 Reorder the terms: -5 + p = 9 Solving -5 + p = 9 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + p = 9 + 5 Combine like terms: -5 + 5 = 0 0 + p = 9 + 5 p = 9 + 5 Combine like terms: 9 + 5 = 14 p = 14 Simplifying p = 14
| 2x^2-11x+30=0 | | 15x+6=4x-5 | | 87-5x=31x+23 | | 6-7x= | | 63-3x=9x+20 | | 1+9=49+x | | 6x+29=6x+3 | | 2x+3=-5x+9 | | x+2x+3=7 | | 2+=4 | | 2x+1-3x=-4 | | 2k-3=k+2 | | 13x^2=64 | | 10-x=1.5x-5 | | 5-5y=-20 | | 2x-6x=12 | | -5-5y=20 | | 3(2)+2y=0 | | 3(-2)+2y=0 | | 3(0)+2y=0 | | 5x-4=2x+17 | | 5a-3b-2a+6+7b= | | 20+4x=14x-10 | | 4(0)+y=3 | | 29x+20y=4 | | 4(-1)+y=3 | | 4(1)+y=3 | | 2x^2-7=6 | | A={0,1,2} | | 2w+4=4w-5 | | 201-6x=6x+21 | | 2x+4x+34=67 |